Evaluation of the physical and organizational aspects of the family health unit in the community of Vila São Miguel - Afogados - Recife / PE - Elaine Judite de Amorim Carvalho; Geane Nário de Souza; Hellencleia Pereira Cunha; Lucineide Cristina Barbosa; Raissa Pires Morais; Rafaela Valadares Amorim; Vera Lúcia Ramos da Silva; Sheila Amarantes do Nascimento; Jacira Maria da Conceição (Universidade de Santa Cruz do Sul, 2012)
Rationale and Objectives: There are several reasons why the family health strategy does not address the needs of the community, as there are factors that infl uence the low quality of the offered services. The aim of this study was to establish the diagnosis of community and the Family Health Unit (FHU) of Vila São Miguel - Afogados - Recife / PE, regarding the provision of health services. Methods: The present is an descriptive quantitative study. Two questionnaires were used, the fi rst being directed to six health professionals and the second, to 150 users of the unit. Results: When analyzing the data related to health professionals, it was observed that with regard to work infrastructure and organization, the FHU corresponded to less than 50% of what is considered appropriate, but regarding health care, the team showed an excellent performance (70%). In the second questionnaire, a user profile was observed, showing that 82.24% have lived in the community for more than 10 years and 33.56% go to the FHU monthly. Regarding the capacity of the FHU to receive disabled individuals, 81.45% responded that the unit has no necessary physical infrastructure; 82.55% said they not participate in any educational activity of the FHU and 66% said they never requested a visit from a team professional. As for consultations, 51% can schedule them monthly for a doctor's appointment, 27.9% for nursing and 16.55% for dentistry; 42.95% reported they never need to perform a gynecological, blood, urine or stool examination at FHU. Conclusion: The FHU was well appraised on most items, with the most critical point being accessibility to individuals with disabilities. KEYWORDS: Evaluation. Health Services. Family Health.